Studi Waktu Polinasi terhadap Keberhasilan Persilangan pada Tanaman Padi Beras Merah dan Beras Putih (Oryza Sativa L.) - Neng Nadia Rahayu; Darso Sugiono; Yayu Sri Rahayu; Heni Safitri; Puji Lestari (Peneliti.net, 2022)
Pollination is a key factor in achieving high yields in hybridization. However, rice pollination is a very sensitive process because it is related to the receptive period of the flower. In general, the recommendation for pollination time is 10:00-12:00 the day after emasculation. Seeing the basis of pollination time which is only carried out within one day is an opportunity to test the difference in pollination time, this aims to find out how long the pistil can remain receptive and to know when the pollination time is right. The research was conducted at IP2TP, Bogor. The method used was Completely Randomized Design (CRD) with 2 factors. Analysis data result used ANOVA test and further testing with DMRT 5% levels. Treatment S6W1 gave the highest yield of 48.33 grains, significantly different from all treatments. The second highest result was obtained from S1W1 but not significantly different from S6W2, S4W1, S3W1, S6W3 and S5W1. The inclusion of pollination time 2 and 3 days after emasculation in the ranks of the second-highest yielding success of the cross can be categorized that pollination time can be carried out 2 or 3 days after that although there is a decrease in yield.